2013
DOI: 10.1007/s10162-013-0380-5
|View full text |Cite
|
Sign up to set email alerts
|

Congenital and Prolonged Adult-Onset Deafness Cause Distinct Degradations in Neural ITD Coding with Bilateral Cochlear Implants

Abstract: Bilateral cochlear implant (CI) users perform poorly on tasks involving interaural time differences (ITD), which are critical for sound localization and speech reception in noise by normal-hearing listeners. ITD perception with bilateral CI is influenced by age at onset of deafness and duration of deafness. We previously showed that ITD coding in the auditory midbrain is degraded in congenitally deaf white cats (DWC) compared to acutely deafened cats (ADC) with normal auditory development (Hancock et al., J. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 69 publications
(102 reference statements)
7
43
6
Order By: Relevance
“…This is a well-known phenomenon, related with the reduced survival rate of spiral ganglion cells in postmeningitic cochleas. [28][29][30] The personal experience with CIs after long-term deprivation was also quite disappointing: in agreement with the literature [31][32][33], none of our pre-verbal children receiving a CI after 10 years of age ever equalled the speech perception performances of earlier CI recipients (below 3 years of age at surgery).…”
Section: Discussionsupporting
confidence: 83%
“…This is a well-known phenomenon, related with the reduced survival rate of spiral ganglion cells in postmeningitic cochleas. [28][29][30] The personal experience with CIs after long-term deprivation was also quite disappointing: in agreement with the literature [31][32][33], none of our pre-verbal children receiving a CI after 10 years of age ever equalled the speech perception performances of earlier CI recipients (below 3 years of age at surgery).…”
Section: Discussionsupporting
confidence: 83%
“…For example, ultrastructural studies in congenitally deaf cats have shown that neurons in the medial superior olive, a brainstem nucleus involved in processing interaural time differences, exhibit abnormalities in the number and size of their synaptic inputs, which can be partially reversed after prolonged intracochlear electrical stimulation (Tirko and Ryugo, 2012). Recordings from neurons in the inferior colliculus of bilaterally implanted adult animals have demonstrated that ITD sensitivity in congenitally deaf cats is degraded compared with that seen in acutely deafened animals (Hancock et al, 2010(Hancock et al, , 2013. Because neural ITD coding was less severely altered in cats that were deafened as adults 6 months before recording (Hancock et al, 2013), it appears that early auditory experience is critical for the development of neural sensitivity to this localization cue.…”
Section: Effects Of Hearing Loss On the Developing Auditory Brainmentioning
confidence: 99%
“…Recordings from neurons in the inferior colliculus of bilaterally implanted adult animals have demonstrated that ITD sensitivity in congenitally deaf cats is degraded compared with that seen in acutely deafened animals (Hancock et al, 2010(Hancock et al, , 2013. Because neural ITD coding was less severely altered in cats that were deafened as adults 6 months before recording (Hancock et al, 2013), it appears that early auditory experience is critical for the development of neural sensitivity to this localization cue.…”
Section: Effects Of Hearing Loss On the Developing Auditory Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is most relevant to cases of adult-onset deafness of relatively short duration to minimize developmental abnormalities and degenerative changes in the binaural pathways resulting from prolonged deafness (Hancock et al 2010(Hancock et al , 2013Tillein et al 2010). Specifically, we hypothesize that the limitations on ITD sensitivity in single cells in acutely deafened animals and postlingually deaf human subjects could be mainly due to the abnormal properties of auditory nerve fiber (ANF) responses to electric stimulation.…”
Section: Introductionmentioning
confidence: 99%